NEW ASPECTS OF MOXONIDINE USAGE IN FEMALE PATIENTS WITH ARTERIAL HYPERTENSION AND POSTMENOPAUSE - E. N. Dudinskaya; O. N. Tkacheva; I. D. Strajesko (Кардиоваскулярная терапия и профилактика, 2014)
The review of a new data is provided related to novel aspects of moxonidine use in the patients with arterial hypertension. The main attention is paid to the problem of vascular ageing, telomere biology, insulin resistance and calcium-phosphorum homeostasis. The possible ways to influence this processes are discussed.